Prevalence and correlates of intimate partner violence among men in a rural community of Oyo State, South-West Nigeria - Ajibola, Idowu; Aderonke, Olumide; Olatayo A., Aremu; Funmito O., Fehintola; Gbenga, Popoola (International Journal Of Community Medicine And Public Health, 2017)
Background: Perpetration of intimate partner violence (IPV) has continued unabated in many parts of the world including Nigeria with women being the victims in most instances. It is scientifically imperative to understand facilitating factors among men. This study examined the prevalence and the determinants of IPV practice among men in a rural community of Nigeria. Methods: This cross-sectional study was conducted among 430 men in Eruwa community, Oyo State, South-Western Nigeria. Two-staged cluster sampling technique was used to recruit study participants. A pre-tested, interviewer administered questionnaire was used for data collection. Data were analyzed using descriptive and inferential statistics. The level of statistical significance was set at p<0.05 and 95% confidence intervals were obtained to assess the determinants of IPV practice. Results: Almost three-quarter (74%) of men had perpetrated one form of IPV or the other prior to the survey. Psychological IPV had the highest prevalence of 67.2%. At the bi-variate level, practice of IPV was significantly associated with respondents’ age (p=0.001), their educational status (p=0.001), employment status (p=0.001), marital status (p=0.001), duration of relationship (p=0.001), attitudes towards IPV perpetration (p=0.001) and age of partners (p=0.001). However, only respondents’ attitude towards IPV practice (OR; 3.10, 95% CI; 1.70-5.74) and their marital status (OR; 0.43, 95%CI; 0.27-0.70) were the significant predictors of IPV practice among the respondents. Conclusions:The burden of IPV is high among men. There is urgent need for policy formulation and implementation to curtail this public health challenge particularly among rural based men.